Modal Sosial Masyarakat Multikultural: Persepsi Komunitas di Dusun Sumberjo, Kabupaten Kediri - Sunarno; Zakiyah, Arisa Rahmawati (Universitas Brawijaya, 2024)
The social capital of the multi-religious community in Sumberjo Village, Kediri Regency which is the cause of harmony is an interesting social phenomenon. This research aims to understand the social capital of multicultural communities and to find out the role of social capital of multicultural communities in Sumberjo, Kediri Regency in inter-religious harmony. The research method used is qualitative with a case study model. The informants numbered 8 residents, with the characteristics of 1 Hamlet Head, 3 residents of different religions, and 4 interfaith youth leaders. Data mining techniques in this research used interviews, observation and documentation. The results of the research are first, the social capital possessed by the community includes having the goal of living together, namely living in harmony, the community has the principle of neighborly living, namely by taking steps, religion for the residents is a personal matter, having meeting spaces between residents in the form of various activities, and residents practice mutual cooperation in community life. Second, the social capital possessed by residents plays a role in creating a harmonious and peaceful life (ayem).